Overview of Eclampsia at a Tertiary Care Hospital - Shakya, B; Vaidya, A (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The aim was to study about the morbidity and mortality of eclampsia cases at Paropakar Maternity and Women’s Hospital, Kathmandu, Nepal. Methods: This is a retrospective study undertaken at Paropakar Maternity and Women’s Hospital, Kathmandu, Nepal on 45 eclampsia cases between14 April 2010 to 16 July 2011. Results: Out of 31,674 obstetric admissions, 45 (0.14%) were eclampsia cases of which 42.2% belonged to 20 - <25 years and 28.8% in 17- <20 years age group occurring mostly in primipara (71.1%). Antepartum and postpartum eclampsia were 77.7% and 22.2% respectively. Majority of them presented at 36-40 weeks’(46.6%), unbooked cases being 80% and 20% had antenatal check-up at this hospital. The diastolic blood pressure on admission recorded was 110-130 mmHg (55.5%), headache being the most common symptom(53.3%), blurred vision (22.2%), HELLP syndrome (4.4%) and urine albumin 3+ (46.6%) at the time of admission. Magnesium sulphate was used as anticonvulsant, loading and maintenance dose (40%) and only as loading dose (33.3%). Though fetal outcome was normal in 44.4% cases, rest were premature (24.4%), intrauterine growth restriction (17.7%) and intrauterine fetal demise (13.3%). Three (6.6%) cases were referred to multidisciplinary center. Maternal mortality occurred in two (4.4%) cases (cardiopulmonary arrest and prolonged hypoxia). Conclusions: When patients with eclampsia presented late, significant morbidity like HELLP syndrome, renal failure and central nervous disorder occurred and muti-organ damage leading to maternal mortality. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 46-49 DOI: http://dx.doi.org/10.3126/njog.v8i2.9770